PERAN KEPERCAYAAN DAN SIKAP TERHADAP MOBILE SHOPPING UNTUK MENINGKATKAN NIAT PEMBELIAN ULANG - Ken Sudarti; Annissa Aprilia Sari (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
The world has now entered the era of the Industrial Revolution 4.0, where in this era the world was colored by artificial intelligence (artificial intelligence), genetic engineering, nanotechnology, innovation, and changes that occurred rapidly had an impact on the economy, industry, government, and politics. Industry 4.0 is more likely to lead to business activities using digital platforms such as mobile shopping, e-commerce, marketplaces, and so on. The characteristic of online shopping is that it must be simple and fun, and with a very varied platform can increase its own trust in consumers to shop online. This study aims to develop the concept of a business platform that can affect the perceived usefulness and perceived enjoyment of the millennial generation in online shopping. This concept focuses on one's repurchase intention to do online shopping which is influenced by the existence of so many business platforms and provide different services. The population used is characteristic of the millennial generation in Central Java. This sampling technique using purposive sampling method. The samples used amounted to more than 100 millennials in Central Java, and who frequently use business platforms/applications in online shopping. Data analysis techniques using regression with SPSS